# Verify that $x^{3}+y^{3}+z^{3}-3 x y z=\frac{1}{2}(x+y+z)\left[(x-y)^{2}+(y-z)^{2}+(z-x)^{2}\right]$

AcademicMathematicsNCERTClass 9

#### Complete Python Prime Pack for 2023

9 Courses     2 eBooks

#### Artificial Intelligence & Machine Learning Prime Pack

6 Courses     1 eBooks

#### Java Prime Pack 2023

8 Courses     2 eBooks

To do:

We have to verify that $x^{3}+y^{3}+z^{3}-3 x y z=\frac{1}{2}(x+y+z)\left[(x-y)^{2}+(y-z)^{2}+(z-x)^{2}\right]$.

Solution:

We know that,

$a^3 + b^3 + c^3 - 3abc = (a + b + c) (a^2 + b^2 + c^2 - ab - bc - ca)$

Therefore,

LHS $=x^{3}+y^{3}+z^{3}-3 x y z=(x+y+z)(x^2 + y^2 + z^2-xy-yz-zx)$

$= \frac{1}{2}(x+ y+ z)[2(x^2 + y^2 + z^2 - xy- yz - zx)]$

$= \frac{1}{2}(x+ y+ z)(2x^2 + 2y^2 + 2z^2 - 2xy- 2yz - 2zx)$

$= \frac{1}{2}(x+y+z)(x^2 + x^2 + y^2 + y^2 + z^2 + z^2 - 2xy - 2yz - 2zx)$

$= \frac{1}{2}(x+y+ z)(x^2 + y^2 - 2xy+ y^2 + z^2 - 2yz+ x^2 + z^2 -2zx)$

$= \frac{1}{2}(x+y+z)[(x-y)^2 + (y-z)^2 + (z-x)^2]$

$=$ RHS

Hence, $x^{3}+y^{3}+z^{3}-3 x y z=\frac{1}{2}(x+y+z)[(x-y)^2 + (y-z)^2 + (z-x)^2]$.

Updated on 10-Oct-2022 13:39:07

Advertisements